Diseño y evaluación hidrológica del tramo del eje vial Guadalupe-Caballo Blanco del plan vial de la ciudad de Cartago a la altura de Dulce Nombre - Navarro-Pacheco, Marlon (Instituto Tecnológico de Costa Rica, 2009)
This project examines and tries to give a solution to a specific case of flooding problems in Dulce Nombre, Cartago; to this end were the following objectives:  Undertake a preliminary review of available information related to the taxation area.  Assess, review and geo original geometric layout.  Designing the definitive route Altitude.  Perform geotechnical studies necessary while also calculates and quantifies the earthmoving.  Assess and parameterize the tributary area associated with geographic information system. Estimating peak flows from storms related to sources of information available. Sizing and designing hydraulic works necessary.  Designing the surface rolling road stretch covered. The methodology consisted of analysis of information, generation of tables from this, estimates of data, models and simulations results. The results were: a summary of information gathered, redesign of the layout geometry of the axis road between Cartago and south side of the road ITCR Paraíso-Cartago, characterization and physical parameters of the catchment flood flow generator, for obtaining hyetograph Cartago, design of hydraulic project transportation to the Toyogres river, estimation of earthmoving, design thickness of pavement structure and cost estimates for major work.
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Construcción, 2009.
Keywords: Hidráulico; Hidrología; Picos; Flujo; Pavimento